Male care status influences the risk-taking decisions in a glassfrog - Valencia-Aguilar, Anyelet [UNESP]; Rodrigues, Domingos de Jesus; Prado, Cynthia P. A. [UNESP] (Springer, 2020)
Parental care increases offspring survival, but may impose costs by decreasing adult survival or mating opportunities. Because individuals have limited resources, time allocation and risk decisions are expected to vary according to the care status and threat faced by parents. Herein, we evaluated the sources of mortality of clutches of the glassfrogHyalinobatrachium cappelleiand the importance of paternal care for offspring survival. We also compared time allocation patterns and antipredator behavior between attending and non-attending males. Using naturalistic observations and field experiments with different dummy predators, we hypothesized that (1) offspring survival would be positively correlated with paternal care; (2) attending males would spend most of the time caring for the embryos, while non-attending males would spend more time foraging and calling; (3) attending males would prioritize their own survival when facing a high risk of predation, even with negative impacts on offspring survival. Main sources of embryo mortality included predation and dehydration, and offspring survivorship was almost totally dependent on paternal care. Although non-attending males spent more time calling and foraging, attending males also called and were able to attract females and increase their mating success. However, contrary to our prediction, we found that attending males were more risk-tolerant, increasing not only offspring survival but also their mortality risk. Our findings highlight the importance of the predation risk level on parents' decisions and that the reproductive status may play a significant role in determining antipredator behavior and mating success in glassfrog males. Significance statement In species with parental care, parents face a trade-off between investment in current offspring survival and chances of future reproduction. Hence, it is expected that natural selection will favor parents that attend offspring without incurring in higher risk of predation. We investigated time allocation patterns and behavioral responses to different levels of threat in a glassfrog with paternal care. Using field observations and predation experiments, we found that attending and non-attending males ofHyalinobatrachium cappelleibehaved differently depending on their care status and level of threat. Males were more likely to tolerate high risks only when they were caring for clutches. We also found that the commitment of males to continue caring resulted in higher offspring survival. Parental care behavior increased not only larvae hatching success, but also matting success of attending males, suggesting that paternal care might be under sexual selection.
Keywords: Anura; Hyalinobatrachium cappellei; Time allocation; Paternal care; Predation risk; Offspring survival